Model Supervisi Kepala Sekolah dalam Pembinaan Karier Tenaga Kependidikan di SMAN 1 Kaway XVI, Aceh Barat - Jamali, Yusra; Maulita, Riska; Jasmadi, Jasmadi; Agustizar, Agustizar (LaKaspia, 2025)
The low quality and performance of school administration personnel will have an impact on the smooth implementation of education, this happens because employees lack discipline and the most important problem that occurs is the lack of school administration personnel who are in accordance with qualifications. The purpose of this study is to analyse the performance standards of school administration personnel, the principal's steps in coaching school administration personnel, and the achievements in coaching school administration personnel at SMA Negeri 1 Kaway XVI West Aceh. This research uses a qualitative method with a descriptive analysis approach. Data collection techniques were carried out by means of observation, interviews and documentation. The subjects in this study were the principal and 3 (three) school administration personnel. Based on the research results: 1) Performance standards of school administration personnel at SMA Negeri 1 Kaway XVI West Aceh such as correspondence administration, personnel administration, financial administration, infrastructure administration. 2) The steps in coaching given by the principal to school administration personnel are a) Gathering school administration personnel, b) Providing direction coaching to school administration personnel, c) Controlling the implementation of the duties of school administration personnel, and d) conducting evaluations. 3) School administration personnel have not yet obtained achievements in the school administration section.